Penerapan Program SI-PANDAI Sebagai Inovasi Pemberdayaan Kesiapsiagaan Pertolongan Pertama Dalam Situasi Bencana - Raharjo, Bambang Budi; Nugroho, Efa; Nisa, Alfiana Ainun; Rachmawati, Latifah; Istiada, Ayu (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Persons with disabilities are a vulnerable group that often face barriers in emergency situations, including disasters. Therefore, strengthening preparedness capacity needs to be carried out from an early stage. The SI-PANDAI program (First Aid Preparedness for Disability Companions) was implemented as an empowerment effort to improve basic first aid knowledge and skills at the elementary level of Special Schools (SLB) in Pekalongan Regency. The activities were conducted through socialization, demonstrations, simulations, and hands-on practice using a participatory learning approach. Program evaluation was carried out through observation of student engagement and feedback from teachers. The results showed that students actively participated in all training sessions, were able to practice simple first aid steps such as treating minor wounds, performing basic evacuation, and recognizing disaster warning signs. SLB teachers responded positively, stating that the program was beneficial and should be continued sustainably. In conclusion, the implementation of SI-PANDAI proved effective as an adaptive empowerment innovation for first aid preparedness among children with special needs and has the potential to support the development of disaster-resilient inclusive schools.